Protecting Data Privacy Beyond the Trusted System of Record - White, Bill; Moore, Mark; Wilson, Phillip; Yan, Eva (IBM Redbooks, 2020)
To help you safeguard your sensitive data and provide ease of auditability and control, IBM introduced a new capability for IBM Z® called IBM Data Privacy Passports. It can help minimize the risk and impact of data loss and privacy breaches when collecting and storing sensitive data. Data Privacy Passports can manage how data is shared securely through a central control of user access. Data Privacy Passports can protect data wherever it goes. Security policies are kept and honored whenever the data is accessed. Future data access may be revoked remotely via Data Privacy Passports, long after data leaves the system of record, and sensitive data may even be made unusable simply by destroying its encryption key. Data Privacy Passports is designed to help reduce the time that is spent by staff to protect data and ensure privacy throughout its lifecycle via a central point of control. This IBM Redguide presents a business view of Data Privacy Passports, including how data privacy and protection concerns are addressed. We also explore how value is gained through various business model examples.
Online resource; Title from title page (viewed April 14, 2020)
Keywords: Computer security; Information technology -- Security measures; Data protection; Privacy, Right of; Computer systems -- Access control; Sécurité informatique; Technologie de l'information; Sécurité; Mesures; Protection de l'information (Informatique); Systèmes informatiques; Accès; Contrôle; Information technology; Security measures; Computer systems; Access control